2011
DOI: 10.1590/s1413-81232011001100030
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative environmental health research: an analysis of the literature, 1991-2008

Madeleine Kangsen Scammell

Abstract: Resumo Pesquisa qualitativa usa dados não numéricos para entender opiniões, motivos e cren-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…23 A community-engaged approach, which involves the inclusion of community members as partners in all stages of the research, 24 can be effective in identifying and minimizing health effects related to environmental exposures by building capacity, resources, and skill sets within communities. 2527 A community-engaged framework also bridges the gap between academic institutions and communities to allay misconceptions, fears, or suspicions. 25 Each partner contributes unique skills and knowledge to the project to initiate sustainable, effective change that is relevant to the communities’ health needs.…”
Section: Introductionmentioning
confidence: 99%
“…23 A community-engaged approach, which involves the inclusion of community members as partners in all stages of the research, 24 can be effective in identifying and minimizing health effects related to environmental exposures by building capacity, resources, and skill sets within communities. 2527 A community-engaged framework also bridges the gap between academic institutions and communities to allay misconceptions, fears, or suspicions. 25 Each partner contributes unique skills and knowledge to the project to initiate sustainable, effective change that is relevant to the communities’ health needs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, social scientists, specifically medical sociologists and environmental sociologists who have had a long tradition of successful collaboration with community organizations and/or activists, brought new solutions, partnerships and collaborations to mitigate the financial impacts of living in a contaminated community (Senier et al 2008). Scammell (2010) investigated the use of qualitative data in environmental exposures and human health studies to determine whether collaborative efforts between environmental health and social scientists led to an increased understanding of exposures and environmental health outcomes. Scammell observed that 70 out of the 91 articles included multiple authors and from three or more institutions or disciplines within a university and concluded that qualitative data has the potential to improve our understanding of complex exposure pathways, including the influence of social factors on environmental health and health outcomes (Scammell 2010).…”
Section: 0 Environmental Research Translationmentioning
confidence: 99%
“…Scammell (2010) investigated the use of qualitative data in environmental exposures and human health studies to determine whether collaborative efforts between environmental health and social scientists led to an increased understanding of exposures and environmental health outcomes. Scammell observed that 70 out of the 91 articles included multiple authors and from three or more institutions or disciplines within a university and concluded that qualitative data has the potential to improve our understanding of complex exposure pathways, including the influence of social factors on environmental health and health outcomes (Scammell 2010). …”
Section: 0 Environmental Research Translationmentioning
confidence: 99%
“…However, the bulky nature of qualitative data should be seen as a strong point, because such data is more informative, richer and offers a deeper understanding of the problem than quantitative data (Shamai, 2003;Shank and Villella, 2004;Tewksbury, 2009). This is because it allows the voice of participants to be heard (Scammell, 2010) which is fundamental in solving practical problems using applied research. Moreover, this discussion agrees with Miles and Huberman (1994) who assert that words, especially organized into incidents or stories, have a concrete, vivid, meaningful flavour that often proves far more convincing than pages of summarized numbers.…”
Section: Analysis Of the Pathologiesmentioning
confidence: 99%
“…According to Sandelowski and Barroso (2002), Ryan et al (2007), and Roth and Mehta (2008) qualitative research does not regard truth as objective, but as a subjective reality that is experienced differently by each individual. This explains why qualitative researchers assume that human behavior is always bound to the context in which it occurs (Merriam, 2009;Scammell, 2010) and therefore, behaviour must be studied holistically rather than being manipulated (Perone and Tucker, 2003). Subjective meanings have to be attached to the scientific enquiry (Krefting, 1991), because reality is ultimately subjective (Broom and Wills, 2007).…”
Section: Rationale For Interpretivism In Healthcare Researchmentioning
confidence: 99%